THEORETICAL FRAMEWORK OF INTERCUCTURAL COMPETENCE ASSESSMENT TOOLS - A. Gencheva-Vasileva (Trakia Journal of Sciences)
The modern globalized and digitalized world required coaches and physical education pedagogues to apply different elements of intercultural competence in their everyday professional life. This necessitated the need for specialized training. PURPOSE: The goal of the present theoretical analysis was to provide detailed understanding and identify key components of various questionnaires in order to build-up a pedagogical model for acquiring intercultural competence among students in the field of sport and physical education. We have chosen to review validated and reliable tools, which would give us a complete picture related to our future research and model testing. METHODS: We have done a comparative theoretical analysis based on reliability, structure dimensions, and scope of the questionnaires. We have outlined specific features, strengths and weaknesses. RESULTS: As a result, we have revealed the existence of many assessment tools of intercultural competence but they need to be precisely selected and described in order to their potential usage in different contexts. Furthermore, the tools used independently could not give accurate and reliable information. They should be an integrated part of the global assessing model in accordance with the measurement goal. CONCLUSION: Referring to the comparative theoretical analysis, we could conclude that good and detailed knowledge about the content of existing assessment tools is a prerequisite for effective design of test batteries for measuring intercultural competence.